2016
DOI: 10.1002/adsc.201600833
|View full text |Cite
|
Sign up to set email alerts
|

A Catalyst‐Directed Remote Stereogenic Center Switch During the Site‐Selective Aldol Desymmetrization of Cyclohexanone‐Based Diketones

Abstract: Site-selectivity, differentiating members of the same functional group type on one substrate, is an emerging tactic for shortened advanced building block and biomolecule synthesis. Despite its potential, site-selectivity remains less studied and especially so for ketone-based substrates. During this work ketone site-selectivity has been coupled with the chiral amine-catalyzed aldol desymmetrization of 4-keto-substituted cyclohexanones, allowing three stereogenic centers to form in the aldol product while leavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…[9] The technique is both relevant to our work and appealing because we often recovered starting material. [15] Gong was the first to report enamine based desymmetrizations of 4-substituted cyclohexanones exemplified by 1 a-d. [17][18][19] But, our demonstrations are the first to move beyond simple 4-alkyl or 4-phenyl substituted cyclohexanones, and so should increase the application utility. Remarkably, aldol product formation supersedes Knoevenagel and enaminone formation.…”
Section: Resultsmentioning
confidence: 98%
“…[9] The technique is both relevant to our work and appealing because we often recovered starting material. [15] Gong was the first to report enamine based desymmetrizations of 4-substituted cyclohexanones exemplified by 1 a-d. [17][18][19] But, our demonstrations are the first to move beyond simple 4-alkyl or 4-phenyl substituted cyclohexanones, and so should increase the application utility. Remarkably, aldol product formation supersedes Knoevenagel and enaminone formation.…”
Section: Resultsmentioning
confidence: 98%
“… Regioselective mono‐aldol reaction of diketones [48c,d] . [a] Isolated yields of a single diastereomer.…”
Section: Regioselective Mono‐aldol Reactions Of Di‐ or Higher‐ketonesmentioning
confidence: 99%
“…Miss assigned structures have occasionally followed [137] . Interestingly, chiral amine catalyst tuning has shown that diastereomer III (Scheme 10) can be formed in high ee and mediocre yield, albeit with approximately equal quantities of diastereomer I concomitantly forming [48d] …”
Section: Specific Ketones and Their Reaction With 4‐nitrobenzaldehyde...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notable exceptions were the competition reactions with 4-methylcyclohexanone ( Table 2 , entry 10), cyclopentanone ( Table 2 , entry 11), and TBS-hydroxyacetone ( Table 3 , entry 4). The first is a challenging ketone aldol substrate [ 24 , 25 ] and a single stereoisomer, albeit from eight possible stereoisomeric products, was isolated in only 65% yield. The second, a competition reaction between cyclopentanone/acetylacetone, proceeded with the lowest dr (4:1) of all in-water examples ( Table 2 and Table 3 ) and initially displayed lower diastereoselectivity (2.3:1).…”
Section: Discussion and Resultsmentioning
confidence: 99%